Use of Amberlite Xad-7hp for the Separation of Mn(ii) and Mn(vii) in Waters - Erdem Yayayürük, Aslı; Eroğlu, Ahmet Emin; Eroğlu, Ahmet Emin (Pleiades Publishing, 2017)
A simple method is proposed for the determination and speciation of Mn(II) and Mn(VII) in waters utilizing a macroporous resin, Amberlite XAD-7HP. The batch method was employed and flame atomic absorption spectrometry was used in all determinations. Amberlite XAD-7HP resin was shown to retain Mn(VII) between pH 4 and 12. If the solution contains only one of the species, either Mn(II) or Mn(VII), the resin behaves selectively depending on the pH of the solution. The elution from the sorbent was realized using K2C2O4 in HNO3. The efficiency of the method was checked via spike recovery experiments. The proposed method was successfully applied to industrial wastewater samples and quantitative recoveries (≥96.0%) confirmed the accuracy of the method.
Keywords: Manganese; Speciation; Atomic absorption spectrometry; Amberlite XAD-7HP; Macroporous resin